Designing the Interventions to Mitigate the Barriers of Coordination in Handling Food Security: Insight from Central Java Province - Aries Susanty; Novie Susanto; Hanifa Denny; Yulianto Prabowo; Regine A. S. Permadi; Ayu Fauziyah (Journal of Food Quality)
This study aims to identify the underlying barriers that may prevent public policy coordination among stakeholders in dealing with food security in Central Java Province and suggest recommendations to enhance the coordination. This study used primary data from a questionnaire that the six government agencies’ experts filled out. These experts were asked to identify the relevance and the importance of each barrier and formulate a suitable policy recommendation. There were three data processing techniques used in this study: Content Validity Analysis, Interpretative Structural Modelling (ISM) Method, and Delphi Method. The result of the Content Validity Analysis indicated 22 valid barriers. The result of the ISM method indicated eight barriers occupied the topmost level (complicated problems, insufficient sharing of information, ambiguities and lack of clarity, gap of coordination implementations between the rules and policies with the actual practice, fewer budget allocations, different aims and priorities, lack of motivation to collaborate among stakeholders from various disciplines, and weak of infrastructure). The result of the ISM method also indicated three “very significant” barriers: inadequate human resources, the limited capability of the regional government, and lack of communication and high specialization in multisector collaboration. Then, the result of the Delphi Method indicated several recognize policies to mitigate those barriers. Moreover, related to the limitation of this study, future studies should focus on the barriers in diverse places nations or compare different regions or countries; include more experts from the various stakeholder group, and test the recognized policies in the real world.